THE EFFECT OF LOKALATE PRODUCT QUALITY ON THE CUSTOMER LOYALTY THROUGH BONUS PACK PROMOTION IN JAMBI CITY - Dara Sonia; Syahmardi Yacob; Musnaini Musnaini (Management Department, Faculty of Economics and Business, Universitas Jambi, 2021)
The research purpose is to examine the effect of Local Product Quality on Customer Loyalty through Bonus Pack Promotion at Jambi City. Delivery questionnaires with several 125 respondents carried out the data collection. The data testing techniques used validity and reliability tests, R-square tests, and hypothesis testing—the research finds that Local Product Quality has a positive and significant effect on Customer Loyalty. Local Product Quality has a positive and significant impact on Bonus Pack Promotion. Moreover, Bonus Pack Promotion has a positive and significant impact on Customer Loyalty. However, Local Product Quality on the Customer Loyalty through Bonus Pack Promotion has no effect.